Relationship between Perception of Village Cadre's Interpersonal Communication and Health Service Satisfaction - Dede Yuliarti; Firman Parlindungan (IJELR: International Journal of Education, Language, and Religion, 2021)
Interpersonal communication is communication that occurs between two or more people, which is usually not formally regulated. In interpersonal communication, each participant uses all elements of the communication process. Village cadres have a very important role in monitoring, controlling and paying attention to the health condition of the community in Keude Tanjong Village, XVI District, West Aceh Regency. The services provided by village cadres with the community at the posyandu are positive and can be well received by visitors at the posyandu, so that the satisfaction achieved gets positive results. This research is quantitative. Respondents who became the target of the study were mothers or people who visited the posyandu in Keude Tanjong village. Data collection using the Likert scale method, in-depth interviews, and using SPSS (Statistical Product and Service Solutions) application access. Analysis of the services provided by village cadres to the community got a good response, but there were also some respondents who did not accept the services provided, so that when they got respondents it was not pleasant, it was marked by negative perceptions of the various characteristics of these things and the triggers of the problem. The results showed that the relationship between interpersonal communication of village cadres and satisfaction with health services at the posyandu between posyandu cadres and the community in Keude Tanjong Village was strongly positive, namely, the relationship between interpersonal communication of village cadres and satisfaction of health services in the same direction where the greater the interpersonal communication relationship of village cadres, it would be the greater the satisfaction of health services in the village of Keude Tanjong.